Implementation of eco-innovation in hotels: A dynamic capabilities approach - Dias, Á.; Lopes da Costa, R.; Pereira, L.; Santos, J. (Tourism, 2021)
In a context of increasing concern with environmental factors, hotels show a tendency to respond with passivity to eco-innovation. Furthermore, the literature is scarce about the way hotels adopt and integrate eco-innovation changes in their internal processes. As such, this article intends to present an integrative perspective of the dimensions that influence the adoption of eco-innovation, starting from the external dimension, which incorporates the context and drivers of eco-innovation. The internal dimension is divided into two levels: ordinary and dynamic capabilities. Based on a survey of a sample of hotels, the data were analyzed using partial least squares. The results indicate a positive and significant relationship between context and drivers in both dynamic and ordinary capacities. The influence of context on the green behaviour of hotels was only found in the technological dimension, while external drivers show a strong correlation with eco-innovation. The results also indicate that the two dynamic capacities and the three ordinary capacities studied have a positive and significant relationship with eco-innovation. The role of knowledge is highlighted, not only by its role in establishing a link with the external dimension, but also in the reconfiguration of the set of implementation capabilities that triggers eco-innovation.